High-power Er:Y2O3 ceramic laser with an optical vortex beam output at ∼ 2.7 μm - Ding, Manman; Wang, Jun; Wang, Fei; Shen, Deyuan; Tang, Dingyuan; Zhu, Heyuan (Frontiers in Physics, 2023)
We report on direct generation of high-power optical vortices at 2.7 μm from an Er:Y2O3 ceramic laser end-pumped by an annular pump beam using a simple capillary fiber-based pump beam conditioning scheme. Taking advantage of the thermal gradient on the gain medium and mode matching between the pump and oscillating modes, vortex beams with controllable topological charge order of l = 1 and l = 2 was successfully achieved. The laser yields 4.65 W of output power at an absorbed power of 19.8 W, corresponding to a slope efficiency of 25.9% with respect to the absorbed pump power. Adaptable beam profiles from a shallow crater-shape to a quasi-top-hat intensity patterns were directly produced by actively defining the gain distribution in the ceramic, generating 4 W shallow crater-shape beams and 3.9 W quasi-top-hat beams, corresponding to a slope efficiency of 22.0% and 22.7%, respectively. Such optical vortices and tailored spatial intensity profiles in the 3-µm spectral region will enable novel applications such as super-resolution molecular spectroscopy and material processing.